Pemanfaatan Raspberry Pi 3 Pada Pembuatan Sistem Absensi Berbasis Pengenalan Wajah - Siti Komariah; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Biometrics is an automatic method for recognizing someone based on physical or behavioral characteristics, including biometric Face Recognition which is generally used for identification and verification. Identification is the process of recognizing and matching of a it is person's biometric data in a database that contains a person's character record. Verification is the process of information determining whether someone is in accordance with his/her look. In this research, a biometric attendance system designed using a tool called Rasberry Pi 3 (Mini Computer) for taking user face images (photo grid) then planting is eigenface algorithms and artificial neural network. Rasberry Pi often abbreviated as Raspi is a single board computer whereas whereas the it’s size same as credit card that can be used to run official programs, computer games and media player for high resolution videos. Eigenface algorithm is used for the process of recognizing facial patterns. Eigenface is an eigenvalue and eigenvector approach. Based on this approach the classification is done to recognize faces in training with objects that have been stored in the database. ANN is used because it has ability to learn from the data trained. With the design of this attendance system, it is expected to avoid negative things, for example, the loss of student attendance data because there are too many signatured papers in the attendence list for each subject. The results of testing face data used 3 hidden layers where the first layer has 32 neurons, the second layer has 18 neurons, and the third layer has 8 neurons. It concludes that the face recognition system succed to recognize somebody’s face as his/her photograph with accuracy of 100%.Keywords : Face Recognition, Raspberry Pi 3, Eigenface, Artificial Neural Network.